Pseudo-Pemphigoid Gestationis Eruption Following SARS-CoV-2 Vaccination with mRNA Vaccine - Caroline de Lorenzi; Gürkan Kaya; Laurence Toutous Trellu (MDPI AG, 2022)
Auto-immune reactions, including auto-immune bullous disease, have been reported following SARS-CoV-2 virus vaccination. Few cases of bullous pemphigoid are described, but there has been no case of pemphigoid gestationis. We report the first case here.